Renal Protective Effect of Beluga Lentil Pretreatment for Ischemia-Reperfusion Injury. (31st January 2021) - Lee, Syng-ook; Chun, So Young; Lee, EunHye; Kim, Bomi; Yoon, BoHyun; Gil, Haejung; Kim, Dae Hwan; Jang, Byung Ik; Lee, Dong Woo; Yoo, Eun Sang; Park, Dong Jin; Lee, Jun Nyung; et al.
Abstract : Background and Aim . Ischemia/reperfusion (I/R) injury, caused by acute kidney damage, causes histopathological alterations, tubule cell apoptosis, inflammation, oxidation, and the loss of renal function. We evaluated the protective effects against I/R injury of beluga lentil pretreatment. Materials and Methods . Mice were divided into four groups: normal, untreated, low- (2 mg), and high-dose (8 mg) beluga lentil treatment groups. Beluga lentil was orally administered for 2 weeks, followed by bilateral renal ischemia for 20 min and reperfusion for 30 min. Blood samples and kidney tissues were collected and analyzed to investigate renal function, histopathology, epithelial and endothelial cell damage, apoptosis, oxidative stress, and inflammatory responses. Results . The pretreated groups maintained renal function, with significantly lower blood urea nitrogen (BUN) and creatinine levels, compared with the other groups. The histopathological analysis showed reduced proximal tubule injury and decreased injury-related molecule (kidney injury molecule 1 (KIM-1) and neutrophil gelatinase-associated lipocalin (NGAL)) secretion in the pretreated groups compared with the other groups. Terminal deoxynucleotidyl transferase dUTP nick-end labeling- (TUNEL-) positive cells and the secretion of apoptosis-related molecules (Fas and caspase 3) were significantly reduced in the pretreated groups compared with the other groups. The pretreated groups showed positive microvessel-associated gene (cluster of differentiation (CD31)) expression and negative adhesion molecule (intracellular adhesion molecule 1 (ICAM-1)) expression. An antioxidant effect was observed in the pretreatment groups, with reduced malonaldehyde (MDA) expression and increased antioxidant enzyme (superoxide dismutase (SOD), catalase (CAT), glutathione (GSH), and glutathione peroxidase (GPx)) secretion. In the pretreated groups, F4/80+ macrophages and CD4+ T cell infiltration were inhibited and proinflammatory cytokine (interleukin- (IL-) 1 β, IL-6, and tumor necrosis factor- (TNF-) α ) levels decreased; however, the levels of anti-inflammatory cytokines (transforming growth factor- (TGF-) β, IL-10, and IL-22) increased. Conclusions . Beluga lentil pretreatment demonstrated protective effects against I/R-induced renal damage, via antiapoptotic, anti-inflammatory, and antioxidant activities.